The Normative Antinomy in the Paradox of Customary Rights Protection in the Vortex of Investment and Structural Agrarian Conflict - Mustika Mega Wijaya; Megawati Barthos (JURNAL AKTA, 2025)
The urgency of this research lies in the pressing need to rectify the antinomy of norms between the protection of customary land rights (hak ulayat) and the neoliberal investment regime following the enactment of the Job Creation Law, which has triggered structural agrarian conflicts. This study aims to deconstruct the distorted interpretation of the State Right of Control (Hak Menguasai Negara), which currently legitimizes state-facilitated land grabbing practices through the Land Bank instrument and licensing bureaucracy. Through critical analysis, this study seeks to formulate legal corrections to realign the direction of agrarian politics with the constitutional mandate of social justice. This research employs a normative legal research method focused on examining the antinomy of norms and dogmatic conflicts between the protection regime for customary law communities and the investment acceleration regime within the national agrarian legal system. The study finds that post-Job Creation Law, the agrarian legal paradigm has shifted drastically toward neoliberalism, distorting the state's function into a commercial agent through the Land Bank. Its implementing regulations operate as a legal ecosystem that facilitates the systematic dispossession of people's land and nullifies public participation for the sake of investment. This reduces the philosophy of land to merely a capital asset, perpetuates structural conflicts, and manifestly betrays the constitutional mandate.